4(f-5)=-24

Simple and best practice solution for 4(f-5)=-24 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 4(f-5)=-24 equation:


Simplifying
4(f + -5) = -24

Reorder the terms:
4(-5 + f) = -24
(-5 * 4 + f * 4) = -24
(-20 + 4f) = -24

Solving
-20 + 4f = -24

Solving for variable 'f'.

Move all terms containing f to the left, all other terms to the right.

Add '20' to each side of the equation.
-20 + 20 + 4f = -24 + 20

Combine like terms: -20 + 20 = 0
0 + 4f = -24 + 20
4f = -24 + 20

Combine like terms: -24 + 20 = -4
4f = -4

Divide each side by '4'.
f = -1

Simplifying
f = -1

See similar equations:

| 2cos^2x=coax | | 32x^2+48x^4=0 | | 8.56x+51.36=102.72 | | -26.7+3.4r=4.4(r-6) | | D(20)=22g | | -10(s+2)=53 | | 6a+11=28+83 | | 9999999999999-24533357= | | Y=4x-260 | | 2x+2x+2=4x+4 | | X+2=10+5x | | 45a+35= | | 7x+-3=39 | | D(10.5)=22g | | 8c-7= | | 3(x-4)squre=27 | | (5m-7)+9m= | | 3(x-4)square=27square | | 3(x-4)=27square | | X-10=101 | | -2x+2=4x+68 | | 2(x+3)=6x-4(x-1.5) | | 3(20-b)=26 | | x(2x-2)+x(5x-2)=(7x+8)(x-2) | | 8+2n-1= | | 21n(5x)=10 | | 5m-4n= | | 14-3c=1 | | 13x+5yi=-52+40i | | 15x^2+9c=0 | | 40=6x*8 | | flozc= |

Equations solver categories